Alkaline earth metal borate birefringent crystal as well as growth method and application thereof
By using Ba2Mg2Tb2(BO3)4O as a birefringent crystal material and controlling process conditions, the problem of difficult and stability of borate ultraviolet birefringent crystal preparation is solved, high-quality and low-cost crystal growth is achieved, and the needs of ultraviolet and deep ultraviolet birefringent technologies are met.
Patent Information
- Application Number
- CN202411916792.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-12-24
AI Technical Summary
In the prior art, the preparation of borate ultraviolet birefringent crystals is difficult, the growth conditions are strict, and stability problems may occur under specific environmental conditions, and performance optimization and industrialization process are not effective.
Ba2Mg2Tb2(BO3)4O is used as a birefringent crystal material, and the growth is carried out through specific molar ratios and process conditions, including preheating at 500°C for more than 24 hours, heating at 940-960°C for 6 hours, cooling to 700°C for preliminary nucleation and growth, and controlling the oxygen flow in the range of 0.6 to 0.7 mL/min.
Birefringent crystals with low cost growth, stable physical and mechanical properties, high transmittance in ultraviolet and deep ultraviolet areas, excellent birefringence coefficient and difficult to detach, filling the lack of birefringent crystal materials in ultraviolet and deep ultraviolet bands, and have broad industrial application prospects.
Smart Images

Figure CN119615368A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of birefringent crystals, and in particular to an alkaline earth metal borate birefringent crystal and a growth method and application thereof. Background Art
[0002] Birefringence refers to the phenomenon that when a light wave is projected onto its interface, two refracted light beams are generated due to the anisotropy of the crystal material. Due to the anisotropy of the crystal material, birefringent crystals are widely used in optics, electronics, biology and other fields. Especially in the field of optics, they are the key to manufacturing polarization devices, optical elements and materials with special optical properties, and are of great significance to improving the performance of optical systems and promoting scientific and technological development.
[0003] The birefringent crystals currently available on the market include CaCO3, YVO4, TiO2, LiNbO3, and α-BBO. Several commonly used birefringent crystals each have their own unique advantages and disadvantages. For example, CaCO3 (Iceland spar) has a significant birefringence effect and good light transmittance, and is suitable for the preparation of optical devices such as polarized light prisms, but its application in the deep ultraviolet spectrum is limited and it is a non-renewable resource. YVO4 has a high birefringence index and a wide light transmittance range, and is widely used in the field of optical fiber communications, but the preparation cost is high and the stability may be affected in certain environments. TiO2 (rutile) has excellent birefringence performance and good wear resistance, but the single crystal hardness is large and difficult to process, and may be chemically corroded. MgF2 has a wide transmission spectrum range and a stable refractive index, but the device size is large, and the stability may be affected in high temperature and high humidity environments. α-BaB2O4 (α-BBO) performs well in the visible and ultraviolet regions and is suitable for the preparation of high-performance ultraviolet optical devices, but it is difficult to obtain high-quality large-size single crystals, and the preparation cost is high. LiNbO3 has excellent nonlinear optical and electro-optical effects, and stable physical and chemical properties, but its birefringence performance may not be as good as other crystals in some applications, and its preparation cost is also relatively high. Therefore, birefringent crystals still have a wide range of exploration in terms of application requirements, cost budget, and preparation process.
[0004] Borates have become candidate materials in the ultraviolet and deep ultraviolet fields due to their short ultraviolet cutoff edge and structural diversity. The BO3 or BO4 structural units in borates can be combined into a variety of structures, giving the material multifunctionality. Its wide transparency range, high laser damage threshold and excellent stability have great potential in the optical field, especially in the deep ultraviolet band. In recent years, technicians in this field have modified the structure of borates to improve their birefringence and ultraviolet transmittance. The relevant research results have shown broad application prospects in the fields of optical devices, laser technology and optical communications, especially in optical devices such as polarized light prisms, optical isolators and prism polarizers. However, the preparation of borate ultraviolet birefringent crystals in the prior art is still difficult, the growth conditions are harsh, and the crystals may have stability problems under specific environmental conditions. At the same time, the performance optimization and industrialization process have not achieved good results.
[0005] In summary, the research and development of new birefringent crystal materials suitable for ultraviolet, especially deep ultraviolet, not only has great scientific significance, but also has urgent practical significance. Summary of the invention
[0006] In view of the problems related to the prior art, the present invention aims to develop a new type of birefringent crystal material, which has not only a simple growth method but also excellent crystal performance to meet the growing scientific research and industrial needs of optical devices.
[0007] In order to achieve the above-mentioned invention object, the technical solution provided by the present invention is:
[0008] An alkaline earth metal borate birefringent crystal, whose chemical formula is Ba2Mg2Tb2(BO3)4O, belongs to the trigonal system, P63CM space group, and the unit cell parameters are
[0009] A method for growing an alkaline earth metal borate birefringent crystal comprises the following steps:
[0010] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were weighed in a molar ratio of 2:1.02-1.07:2:4.2-4.5, the weighed raw materials were placed in a grinding device, and fully ground to form a uniform powder mixture;
[0011] (2) placing the powder mixture in a 100 mL platinum crucible, placing it in a programmable temperature-controlled furnace, and preheating it at 500° C. for more than 24 hours until the components are completely decomposed;
[0012] (3) placing the platinum crucible in a programmable temperature-controlled furnace and heating it to 940-960° C. and maintaining it for 6 hours to promote further reaction and melting of the raw materials to obtain a molten liquid;
[0013] (4) The molten liquid is then cooled to 700°C at a rate of 1.5-1.6°C / h to allow initial nucleation and growth of the crystal. After the crystal grows to a predetermined size, it is lifted out of the melt and finally cooled to room temperature at a rate of 15-20°C / h to obtain a Ba2Mg2Tb2(BO3)4O birefringent crystal.
[0014] In this preparation method, the proportion of each component needs to be strictly controlled. Fine-tuning the proportion of each component will affect the purity and composition of the crystal. Increasing the proportion of BaCO3 will increase the barium content in the crystal, thereby affecting its optical properties. Changes in the proportion of Tb(NO3)3·6H2O will affect the luminescence properties and birefringence effect of the crystal.
[0015] It is also necessary to control the preheating time of the raw materials, the temperature when heated to the melting stage, the cooling rate and other process conditions.
[0016] Prolonging the preheating time helps the complete decomposition and uniform mixing of the raw materials, thereby improving the quality of the crystal. However, too long a preheating time will increase energy consumption and production costs. Insufficient preheating time will lead to incomplete decomposition of the raw materials, affecting the growth and performance of the crystal.
[0017] Increasing the melting temperature helps to accelerate the reaction and melting process of the raw materials, but too high a temperature leads to the volatilization and loss of the raw materials, as well as changes in the crystal structure. Reducing the melting temperature will prolong the melting time and affect production efficiency.
[0018] The cooling rate during the initial nucleation and growth stages has an important influence on the nucleation rate and growth morphology of the crystal. A faster cooling rate promotes the formation of fine nuclei, while a slower cooling rate is conducive to the growth of large crystals. Changes in the final cooling rate will affect the thermal stress and internal defects of the crystal. Too fast a cooling rate causes cracks and stress inside the crystal, while too slow a cooling rate prolongs the production cycle.
[0019] Preferably, during the synthesis of raw materials and the growth of crystals, oxygen is introduced into the program temperature controlled furnace. In the process of the above-mentioned preparation method steps (2), (3), and (4), oxygen is introduced into the program temperature controlled furnace, and the flow rate is 0.6 to 0.7 mL / min. In preheating raw materials and cultivating crystals, high flow oxygen (O2) is a key medium, and the oxygen flow rate significantly affects the crystal growth mechanism. When the oxygen flow rate is lower than 0.5 mL / min, the crystal growth process encounters significant obstacles, and the oxygen concentration of the reaction medium is too low to provide the necessary support for the stable growth of the crystal. With the gradual increase of the oxygen flow rate, that is, from less than 0.5 mL / min to gradually increase to close to 0.5 mL / min and continue to rise, the crystal growth conditions are improved, and the crystal growth becomes smoother, which strongly proves that the appropriate concentration of oxygen plays an indispensable role in the formation and stable growth of crystals. When the oxygen flow rate further climbs to 0.8 mL / min, the crystal quality of the crystal begins to show a deteriorating trend, which is specifically manifested as the difficulty of crystal size control. The oxygen concentration is too high, resulting in excessive chemical reactions in the growth environment, which in turn interferes with the normal growth mechanism of the crystal. Too high oxygen concentration not only does not help the growth of crystals, but will lead to a decline in their performance, which is specifically manifested in unfavorable factors such as reduced crystallinity and uneven size distribution.
[0020] In order to obtain crystals with optimal performance, the oxygen flow rate should be precisely controlled within the range of 0.6 to 0.7 mL / min. Within this flow range, the crystals can achieve stable and high-quality growth, thereby producing single crystal materials with excellent performance.
[0021] Preferably, in the above preparation method, the purity of BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 in step (1) is not less than 99%.
[0022] The present invention also provides the application of alkaline earth metal borate birefringent crystals for ultraviolet bands. The crystal Ba2Mg2Tb2(BO3)4O is used for making ultraviolet / deep ultraviolet optical devices.
[0023] The beneficial effects of the present invention are as follows: The present invention proposes a borate birefringent crystal Ba2Mg2Tb2(BO3)4O and its unique kilosynthesis growth method and application field, aiming to fill the current situation of scarcity of birefringent crystal materials in the ultraviolet and deep ultraviolet bands. The crystal exhibits a number of significant advantages, including low-cost growth, stable physical and mechanical properties, high transmittance in the ultraviolet and deep ultraviolet regions, excellent birefringence coefficient, and non-deliquescent properties. In addition, Ba2Mg2Tb2(BO3)4O crystals are easy to process and cut due to their insoluble properties in water, further enhancing their practical value. These characteristics make the birefringent crystals based on Ba2Mg2Tb2(BO3)4O have broad industrial application prospects in the field of optical communication devices, can meet the needs of ultraviolet and deep ultraviolet birefringence technology, and promote the development of related industries. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to make the purpose, technical solutions and advantages of the present invention more clear, the present invention will be described in detail below in conjunction with the accompanying drawings, wherein:
[0025] Figure 1 This is a picture of Ba2Mg2Tb2(BO3)4O crystal;
[0026] Figure 2 is the transmission spectrum of Ba2Mg2Tb2(BO3)4O crystal;
[0027] Figure 3 This is the birefringence spectrum of Ba2Mg2Tb2(BO3)4O crystal. DETAILED DESCRIPTION
[0028] The present invention is further described in detail below in combination with comparative examples and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention.
[0029] The following raw materials were purchased from Sinopharm Chemical Reagent Co., Ltd., including high-purity (99%) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3.
[0030] Example 1
[0031] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0032] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were weighed accurately in a molar ratio of 2:1.02:2:4.2, and then the raw materials were put into a grinder until they were ground into a fine and uniform powder mixture;
[0033] (2) placing the ground powder mixture into a 100 mL platinum crucible, and then placing it into a programmable temperature-controlled furnace and preheating it at 500 °C for 24 hours to ensure that all raw materials can be completely decomposed;
[0034] (3) After preheating, the furnace temperature was adjusted to 940°C and maintained at this temperature for 6 hours to allow the raw materials to further react and completely melt. At the same time, oxygen was introduced into the furnace at a flow rate of 0.6 mL / min;
[0035] (4) After the melting reaction is completed, the mixture is slowly cooled to 700°C at a rate of 1.2°C / h to provide favorable conditions for the nucleation and growth of crystals. During this process, oxygen is continuously introduced at the same flow rate;
[0036] (5) When the crystal grows to the desired size, stop cooling. Lift the crystal from the liquid surface and cool the remaining melt to room temperature at a rate of 15°C / h. Finally, collect Ba2Mg2Tb2(BO3)4O crystals.
[0037] Example 2
[0038] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0039] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were accurately weighed in a molar ratio of 2:1.05:2:4.35, and fully ground in a grinding device until a fine and uniform powder mixture was formed;
[0040] (2) placing the ground powder in a platinum crucible, placing it in a programmable temperature-controlled furnace, and preheating it at 500° C. for about 24.5 hours, while introducing oxygen at a flow rate of 0.65 mL / min to ensure complete decomposition of the raw materials;
[0041] (3) After preheating, the furnace temperature is raised to 950°C and maintained for 6 hours to promote sufficient reaction and melting between the raw materials. During this process, oxygen is continuously introduced at a constant flow rate;
[0042] (4) Slowly cool to 700°C at a rate of 1.4°C / h to provide a good environment for stable crystal growth;
[0043] (5) When the crystal grows to a predetermined size, the crystal is lifted from the liquid surface, and the remaining melt is cooled to room temperature at a rate of 17.5°C / h to finally harvest Ba2Mg2Tb2(BO3)4O crystals.
[0044] Example 3
[0045] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0046] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 are accurately weighed in a molar ratio of 2:1.07:2:4.5, and fully ground in a grinding device until they are fine and uniform;
[0047] (2) placing the ground powder in a platinum crucible, placing it in a programmable temperature-controlled furnace, and preheating it at 500° C. for 25 hours, while introducing oxygen at a flow rate of 0.7 mL / min to ensure complete decomposition of the raw materials;
[0048] (3) After preheating, the furnace temperature was raised to 960°C and maintained for 6 hours to allow the raw materials to further react and completely melt;
[0049] (4) When the molten liquid stabilizes, it is slowly cooled to 700°C at a rate of 1.6°C / h to allow the crystals to grow smoothly;
[0050] (5) After the crystal grows to the desired size, the crystal is lifted from the liquid surface. The remaining melt is cooled to room temperature at a rate of 20°C / h, and finally taken out from the platinum crucible and cleaned to obtain Ba2Mg2Tb2(BO3)4O crystal.
[0051] By the methods of Examples 1-3, the alkaline earth metal borate birefringent crystals obtained in Example 2 have a moderate growth rate, excellent crystal quality, and the best effect. Example 1 successfully obtains alkaline earth metal borate birefringent crystals. Due to the selection of a lower raw material ratio, melting temperature and cooling rate, as well as a smaller oxygen flow rate, the crystal growth rate is slow, the resulting crystals are of higher quality and have fewer defects, but the crystal preparation cycle is longer. Example 3 adopts the method of this example, the crystal growth rate is faster, and a larger crystal size or higher yield is obtained, but the crystal quality is slightly worse than that of Example 2, and the resulting crystals are prone to local cracking.
[0052] Analysis of the reasons why the crystal quality of Example 2 is the best:
[0053] Raw material ratio: Fine-tuning the molar ratio, such as increasing the ratio of Mg and B, helps to form a more stable crystal structure.
[0054] Preheating time: A slightly longer preheating time (24.5 hours) ensures complete decomposition of the raw materials and reduces impurities during the melting process.
[0055] Melting temperature: A higher melting temperature (950°C) promotes a full reaction between the raw materials and is conducive to the formation of a uniform molten liquid.
[0056] Cooling rate: A moderate cooling rate (1.4°C / h) provides a stable growth environment for the crystals, which is conducive to the orderly arrangement and growth of the crystals.
[0057] Oxygen flow rate: A slightly higher oxygen flow rate (0.65 mL / min) promotes the oxidation decomposition of the raw materials and the release of gas during the melting process, reducing defects in the crystal. The combined effect of these factors makes the crystal quality obtained in Example 2 the best.
[0058] Comparative Example 1
[0059] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0060] (1) First, BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were accurately weighed as raw materials according to the molar ratio of 2:1.1:2:4.3. Then, these weighed raw materials were placed in a grinding device and fully ground until a uniform and fine powder mixture was formed.
[0061] (2) The uniformly ground powder mixture is carefully placed in a 100 mL platinum crucible and then placed in a programmable temperature-controlled furnace. Preheating treatment is performed at a temperature of 500°C for 24.5 hours to ensure that carbonates, hydrated nitrates, and boric acid in the raw materials can be completely decomposed. At the same time, oxygen is introduced into the furnace with a flow rate precisely controlled at 0.65 mL / min to maintain a stable atmosphere in the furnace.
[0062] (3) After preheating, the platinum crucible is placed in a programmable temperature-controlled furnace and heated to 950°C, and maintained at this temperature for 6 hours. This step is intended to promote further reaction and complete melting between the raw materials. During this process, oxygen is continuously introduced at a constant flow rate.
[0063] (4) When the molten liquid reaches a stable state, it begins to slowly cool to 700°C at a rate of 1.4°C / h. This stage is crucial for the nucleation and initial growth of crystals. By precisely controlling the cooling rate, the growth conditions of the crystals can be optimized. Continue to introduce oxygen into the furnace at a constant flow rate.
[0064] (5) When the crystal grows to a predetermined size, the further growth process is stopped and the crystal is lifted off the liquid surface. Finally, the remaining melt is cooled to room temperature at a rate of 17.5°C / h. During the entire process, the oxygen flow rate is always maintained. Finally, the Ba2Mg2Tb2(BO3)4O birefringent crystal is taken out from the platinum crucible and cleaned.
[0065] It is found from this example that the Ba2Mg2Tb2(BO3)4O birefringent crystal prepared in this example has the characteristics of cracking and poor crystallinity. In this example, the ratio of Mg2(OH)2CO3 is too high (1.1) and exceeds the limited range of 1.02-1.07. This leads to an imbalance in the ratio of components in the molten liquid, which in turn affects the crystallization process and stability of the crystal, making the crystal easy to crack and poor in crystallinity.
[0066] Comparative Example 2
[0067] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0068] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 as raw materials are accurately weighed in a molar ratio of 2:1.05:2:4.35, and are put into a grinding device for full grinding until a uniform and fine powder mixture is formed;
[0069] (2) The uniformly ground powder mixture is carefully placed in a 100 mL platinum crucible and then placed in a programmable temperature-controlled furnace. The preheating temperature is adjusted to 550° C. and the preheating time is continued for more than 24.5 hours to ensure that the carbonates, hydrated nitrates and boric acid in the raw materials can be completely decomposed. During the preheating process, oxygen is introduced into the furnace, and the flow rate is precisely controlled at 0.65 mL / min to maintain a stable atmosphere in the furnace.
[0070] (3) After the preheating is completed, the platinum crucible is placed in the programmable temperature-controlled furnace and heated to 950° C. The temperature is maintained for 6 hours to promote further reaction and complete melting of the raw materials to form a uniform molten liquid. During this process, oxygen is continuously introduced at a constant flow rate;
[0071] (4) When the molten liquid reaches a stable state, it begins to slowly cool to 700 °C at a rate of 1.4 °C / h to promote crystal growth;
[0072] (5) When the crystal grows to a predetermined size, further cooling is stopped and the crystal is lifted from the liquid surface. Finally, the remaining melt is cooled to room temperature at a rate of 17.5°C / h. During the entire process, oxygen is always introduced at a constant flow rate. Finally, the Ba2Mg2Tb2(BO3)4O birefringent crystal is taken out from the platinum crucible and cleaned.
[0073] It is found from this embodiment that the Ba2Mg2Tb2(BO3)4O birefringent crystal prepared in this embodiment has the characteristics of cracking and poor crystallinity. In this embodiment, due to the increase in the preheating temperature (adjusted from 500°C to 550°C), the decomposition and melting process of the raw materials will be accelerated, but the too high preheating temperature will cause the raw materials to decompose too quickly or unevenly, generating gas or impurities. These gases or impurities form bubbles or defects during the crystal growth process, causing the crystal to be easy to crack and have poor crystallinity.
[0074] Comparative Example 3
[0075] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0076] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were accurately weighed as raw materials in a molar ratio of 2:1.05:2:4.35, and were fully ground until a uniform and fine powder mixture was formed;
[0077] (2) placing the uniformly ground powder mixture in a 100 mL platinum crucible, placing it in a programmable temperature-controlled furnace, and preheating it at 500° C. for 24.5 hours while introducing oxygen at a flow rate of 0.65 mL / min into the furnace;
[0078] (3) placing the platinum crucible in a programmable temperature-controlled furnace, heating it to 950° C., and maintaining the temperature for 6 hours to promote further reaction and complete melting of the raw materials. During this process, oxygen was continuously introduced at a flow rate of 0.65 mL / min.
[0079] (4) In this step, the cooling rate of the molten liquid is adjusted to 2°C / h, and the molten liquid is slowly cooled to 700°C, and oxygen at a flow rate of 0.65 mL / min is continuously introduced into the furnace;
[0080] (5) When the crystal grows to a predetermined size, the further cooling process is stopped and the crystal is lifted off the liquid surface. Finally, the remaining melt is cooled to room temperature at a rate of 17.5°C / h. During the entire process, the oxygen flow rate is kept constant. Finally, the Ba2Mg2Tb2(BO3)4O birefringent crystal is taken out from the platinum crucible and cleaned.
[0081] It is found from this example that the Ba2Mg2Tb2(BO3)4O birefringent crystal prepared in this example has the characteristic of cracking, because the adjustment of the cooling rate will affect the growth rate and morphology of the crystal. The initial cooling rate (2°C / h) of this example exceeds the given range (1.2-1.6°C / h). Too fast a cooling rate leads to uneven distribution of thermal stress during crystal growth, increasing the risk of crystal cracking.
[0082] Comparative Example 4
[0083] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0084] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were accurately weighed as raw materials in a molar ratio of 2:1.05:2:4.35, and were fully ground until a uniform and fine powder mixture was formed;
[0085] (2) The uniformly ground powder mixture was placed in a 100 mL platinum crucible and placed in a programmable temperature-controlled furnace. Preheating was performed at 500°C for 24.5 hours. During this process, the oxygen flow rate into the furnace was adjusted to 0.4 mL / min.
[0086] (3) After the preheating is completed, the platinum crucible is placed in the programmable temperature-controlled furnace and heated to 950° C., and the temperature is maintained for 6 hours. During this step, oxygen is continuously introduced at an oxygen flow rate of 0.4 mL / min to promote further reaction and complete melting between the raw materials to form a uniform molten liquid;
[0087] (4) When the molten liquid reaches a stable state, it begins to slowly cool to 700°C at a rate of 1.4°C / h. This stage is crucial for the nucleation and initial growth of crystals. During this process, oxygen is continuously introduced at a flow rate of 0.4 mL / min.
[0088] (5) When the crystal grows to a predetermined size, further cooling is stopped and the crystal is lifted from the liquid surface. Finally, the remaining melt is cooled to room temperature at a rate of 17.5°C / h. During the entire process, oxygen is always introduced at a flow rate of 0.8 mL / min. Finally, the Ba2Mg2Tb2(BO3)4O birefringent crystal is taken out from the platinum crucible and cleaned.
[0089] Comparative Example 5
[0090] An alkaline earth metal borate birefringent crystal is prepared according to the following method:
[0091] (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were accurately weighed as raw materials in a molar ratio of 2:1.05:2:4.35, and were fully ground until a uniform and fine powder mixture was formed;
[0092] (2) The uniformly ground powder mixture was placed in a 100 mL platinum crucible and placed in a programmable temperature-controlled furnace. Preheating was performed at 500°C for 24.5 hours. During this process, the oxygen flow rate into the furnace was adjusted to 0.8 mL / min.
[0093] (3) After the preheating is completed, the platinum crucible is placed in the programmable temperature-controlled furnace and heated to 950° C., and the temperature is maintained for 6 hours. During this step, oxygen is continuously introduced at an oxygen flow rate of 0.8 mL / min to promote further reaction and complete melting between the raw materials to form a uniform molten liquid;
[0094] (4) When the molten liquid reaches a stable state, it begins to slowly cool to 700°C at a rate of 1.4°C / h. This stage is crucial for the nucleation and initial growth of crystals. During this process, oxygen is continuously introduced at a flow rate of 0.8 mL / min.
[0095] (5) When the crystal grows to a predetermined size, further cooling is stopped and the crystal is lifted from the liquid surface. Finally, the remaining melt is cooled to room temperature at a rate of 17.5°C / h. During the entire process, oxygen is always introduced at a flow rate of 0.8 mL / min. Finally, the Ba2Mg2Tb2(BO3)4O birefringent crystal is taken out from the platinum crucible and cleaned.
[0096] It is found from comparative example 4 and comparative example 5 that the prepared Ba2Mg2Tb2(BO3)4O birefringent crystal has the characteristics of reduced crystallinity and uneven size distribution, because the oxygen flow rate (0.4mL / min and 0.8mL / min) exceeds the given range (0.6-0.7mL / min). In preheating raw materials and cultivating crystals, high flow oxygen (O2) is a key medium, and the oxygen flow rate significantly affects the crystal growth mechanism. When the oxygen flow rate is lower than 0.5mL / min, the crystal growth process encounters significant obstacles, and the oxygen concentration of the reaction medium is too low to provide necessary support for the stable growth of the crystal. With the gradual increase of oxygen flow rate, that is, from less than 0.5mL / min to gradually increase to close to 0.5mL / min and continue to rise, the crystal growth conditions are improved, and the crystal growth becomes smoother, which strongly proves that the oxygen of suitable concentration plays an indispensable role in the formation and stable growth of crystals. When the oxygen flow rate further climbs to 0.8mL / min, the crystal quality of the crystal begins to show a deteriorating trend, which is specifically manifested as the difficulty of crystal size control increases and the poor crystallinity is easy to crack. Too high oxygen concentration will cause the chemical reaction in the growth environment to be too intense, thus interfering with the normal growth mechanism of the crystal. Too high oxygen concentration will not only fail to help the growth of the crystal, but will lead to a decline in its performance, which is specifically manifested in unfavorable factors such as reduced crystallinity and uneven size distribution.
[0097] Based on the comprehensive analysis of the above experimental results, in order to obtain crystals with optimal performance, the oxygen flow rate should be precisely controlled within the range of 0.6 to 0.7 mL / min. Within this flow range, the crystal can achieve stable and high-quality growth, thereby producing single crystal materials with excellent performance.
[0098] In summary, changes in parameters such as raw material ratio, preheating time, temperature of heating to the melting stage, and cooling rate will have a significant impact on the growth results of alkaline earth metal borate birefringent crystals.
[0099] Therefore, in actual production, these parameters need to be optimized and adjusted according to specific needs and conditions.
[0100] To obtain high quality crystal products.
[0101] Crystal performance test
[0102] The crystal prepared in Example 2 was subjected to a crystal performance test. The crystal belongs to the trigonal system, the P63CM space group, and the unit cell parameters are Figure 1 This is a picture of Ba2Mg2Tb2(BO3)4O crystal.
[0103] Transmission spectroscopy was performed using a 1.5 mm thick Ba2Mg2Tb2(BO3)4O crystal slice and the test results are shown in Figure 2 It can be clearly observed from the figure that in the wavelength range of 250 to 2000 nanometers, the transmittance of Ba2Mg2Tb2(BO3)4O crystals remains stable at more than 80%. When the wavelength is close to 200 nanometers, its transmittance can still reach 40%. It is worth noting that the ultraviolet absorption edge of Ba2Mg2Tb2(BO3)4O crystals is below 200 nanometers, which is close to the 189 nanometers of α-BBO. Therefore, Ba2Mg2Tb2(BO3)4O crystals show great potential as materials for manufacturing deep ultraviolet optical devices.
[0104] Deliquescent test
[0105] In order to explore the deliquescent properties of Ba2Mg2Tb2(BO3)4O crystals, we exposed 5g of the crystal sample that had reached constant weight to air for about a week. After observation, we found that the surface of the sample did not appear wet. The mass was re-measured and the result showed that it was still 5g, with a mass change of less than 0.001g. This test result shows that Ba2Mg2Tb2(BO3)4O crystals have good stability and are not prone to deliquescing.
[0106] Application Examples
[0107] The Ba2Mg2Tb2(BO3)4O crystal prepared in Example 2 was processed into a triangular prism shape, and its refractive index was measured at 12 different wavelengths in the wavelength range of 404.7 nm to 1068 nm. The relevant data have been organized in Table 1. The measurement accuracy of these refractive indices is estimated to be ±2×10-4. Subsequently, we used the least squares method and combined the obtained ne and no values to derive the Se l lmeier dispersion equation, which is specifically expressed as follows:
[0108]
[0109] In the above Sellmeier dispersion equation, λ represents the wavelength and the unit is In order to intuitively present n e (extraordinary refractive index) and n o (ordinary light refractive index) changes with wavelength, such as Figure 3 As shown. At 589 nanometer laser wavelength, the no value of the Ba2Mg2Tb2(BO3)4O crystal is 1.9059, the ne value is 2.0160, and its birefringence is calculated to be -0.1101. This shows that the crystal has good optical properties. Table 1 shows the refractive index at selected wavelengths.
[0110] Table 1 Refractive index at selected wavelengths
[0111] wavelength no ne Birefringence 1.068 1.8789 1.9795 -0.1006 0.9592 1.8821 1.9839 -0.1018 0.8617 1.8851 1.9878 -0.1027 0.8072 1.8874 1.9910 -0.1036 0.6943 1.8958 2.0022 -0.1064 0.6563 1.9000 2.0080 -0.1080 0.5893 1.9059 2.0160 -0.1101 0.578 1.9098 2.0212 -0.1114 0.5461 1.9153 2.0288 -0.1135 0.4962 1.9279 2.0460 -0.1181 0.4861 1.9314 2.0508 -0.1194 0.4047 1.9681 2.1019 -0.1338
[0112] The crystals prepared in Examples 1 and 3 were also subjected to crystal performance testing and application, and the properties exhibited were similar to those of the crystals prepared in Example 2.
[0113] The above-mentioned embodiments illustrate that the birefringent crystal Ba2Mg2Tb2(BO3)4O prepared by the present invention has a number of significant advantages, including low-cost growth, stable physical and mechanical properties, high transmittance in the ultraviolet and deep ultraviolet regions, excellent birefringence coefficient, and non-deliquescent properties. In addition, the Ba2Mg2Tb2(BO3)4O crystal is easy to process and cut due to its insoluble property in water, which further enhances its practical value. These characteristics make the birefringent crystal based on Ba2Mg2Tb2(BO3)4O have broad industrial application prospects in the field of optical communication devices, can meet the needs of ultraviolet and deep ultraviolet birefringence technology, and promote the development of related industries.
Claims
1. An alkaline earth metal borate birefringent crystal, characterized in that: Its chemical formula is Ba2Mg2Tb2(BO3)4O, belonging to the trigonal system, P63CM space group, and the unit cell parameters are 2. A method for growing an alkaline earth metal borate birefringent crystal, characterized in that: The following steps are involved: (1) BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 were weighed in a molar ratio of 2:1.02-1.07:2:4.2-4.5, the weighed raw materials were placed in a grinding device, and fully ground to form a uniform powder mixture; (2) placing the powder mixture in a 100 mL platinum crucible, placing it in a programmable temperature-controlled furnace, and preheating it at 500° C. for more than 24 hours until the components are completely decomposed; (3) placing the platinum crucible in a programmable temperature-controlled furnace and heating it to 940-960° C. and maintaining it for 6 hours to promote further reaction and melting of the raw materials to obtain a molten liquid; (4) The molten liquid is then cooled to 700°C at a rate of 1.5-1.6°C / h to allow initial nucleation and growth of the crystal. After the crystal grows to a predetermined size, it is lifted out of the melt and finally cooled to room temperature at a rate of 15-20°C / h to obtain a Ba2Mg2Tb2(BO3)4O birefringent crystal.
3. The method for growing an alkaline earth metal borate birefringent crystal according to claim 2, characterized in that: During steps (2), (3) and (4), oxygen is introduced into the programmable temperature-controlled furnace at a flow rate of 0.6 to 0.7 mL / min.
4. The method for growing an alkaline earth metal borate birefringent crystal according to claim 2, characterized in that: In step (1), the purity of BaCO3, Mg2(OH)2CO3, Tb(NO3)3·6H2O and H3BO3 is not less than 99%.
5. Use of the alkaline earth metal borate birefringent crystal according to claim 1, characterized in that: The crystal Ba2Mg2Tb2(BO3)4O is used for manufacturing ultraviolet / deep ultraviolet optical devices.
Citation Information
Patent Citations
Borate birefringent crystal for ultraviolet and deep ultraviolet, and growth method and application thereof
CN102839421A
Borate birefringent crystal for ultraviolet band as well as growing method and purpose of same
CN103074684A
Ba3Sc2 (BO3) 4 ultraviolet birefringent crystal, preparation and application
CN115726040A